2020
DOI: 10.1007/s11664-020-08340-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Ni Contents on Thermal Stability of Cu(Ni) Alloy Film

Abstract: The effect of doping different contents of Ni on the thermal stability of Cu(Ni) alloy films has been investigated. Cu(Ni) films with different Ni contents were deposited on SiO 2 /Si substrates by magnetron sputtering, then annealed in vacuum at 350°C to 650°C for 0.5 h. X-ray diffraction analysis and resistance measurements revealed that high-resistance copper silicide was formed after annealing at 450°C for the Cu(Ni, 1.66 at.%) and Cu(Ni, 9.16 at.%) samples. However, no copper silicide was observed for Cu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Notably, the XRD patterns of the barrierless Cu(Ni) and Cu(NiC) alloys annealed at 650 • C did not display any diffraction peaks that corresponded to the copper silicide. Previous research has reported that the interaction between a pure copper film and silicon typically takes place at a temperature of 200 • C, leading to the formation of copper silicide with a notable increase in electrical resistance [1,24]. However, the XRD results of the Cu(Ni) and Cu(NiC) films annealed at 650 • C revealed diffraction peaks only attributed to the existence of Cu.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Notably, the XRD patterns of the barrierless Cu(Ni) and Cu(NiC) alloys annealed at 650 • C did not display any diffraction peaks that corresponded to the copper silicide. Previous research has reported that the interaction between a pure copper film and silicon typically takes place at a temperature of 200 • C, leading to the formation of copper silicide with a notable increase in electrical resistance [1,24]. However, the XRD results of the Cu(Ni) and Cu(NiC) films annealed at 650 • C revealed diffraction peaks only attributed to the existence of Cu.…”
Section: Resultsmentioning
confidence: 94%
“…It is known that Cu and Ni are miscible due to their similar crystal structures, slight differences in atomic radius, and electronegativity [23]. Our previous research has demonstrated that Cu(Ni) alloy has excellent barrier properties [24]. Doped Ni occupies the fast diffusion channel, thereby improving the thermal stability of barrierless Cu films.…”
Section: Introductionmentioning
confidence: 99%
“…The self-formed barrier layer offers low electrical resistivity, resistance to Cu diffusion, resistance to electromigration and compatibility with conformal deposition techniques [16][17][18][19][20][21]. A self-formed barrier scheme is achieved by doping with diffusion barrier elements as well as their nitrides and carbides, such as Ti, Zr, Mn and WN [22][23][24][25][26][27][28]. All these doped elements have low-concentration solutes in Cu, which are supposed to segregate at the interface as a diffusion layer during annealing [16,29].…”
Section: Introductionmentioning
confidence: 99%